The Risk of Bone, Joint and Inflammatory Bowel Disorders in Patients Treated with Angiotensin-Converting Enzyme Inhibitor Drugs - Firas Fadhil Alyaseen (Journal of Global Pharma Technology, 2016)
Objective: the aim of this study is to describe the adverse effects and disorders of angiotensin-converting enzyme inhibitor drugs treatment in patients with various cardiac diseases who prescribed those treatments. It also evaluates the risk of angiotensin-converting enzyme inhibitor drugs on long term therapy of patients. Subjects and methods: this cross-sectional study was carried out in Al Hussein-teaching hospital at Al Nasiriya city, south of Iraq. The research started at November 2016 until April 2017. Eighty one patients (52) males and (29) females], age (34-77 years) were enrolled in this study. All of the patients were diagnosed with cardiac diseases by specialist doctors and currently on angiotensin-converting enzyme inhibitor drugs for long term therapy. The data collected from patients through a questionnaire list designed and developed for this study. The list concerned with the disorders and drugs-related data in addition to the patients' general data. The collected results were analyzed in order to construct tables, figures and other necessary research requirements. Results and conclusions: in this study, most of the cases are treated with angiotensin-converting enzyme inhibitor drugs for hypertension (97.5%), and captopril represents the most popular of them (52 %). The most common significant results among the disorders associated with angiotensin-converting enzyme inhibitor treatment in patients were osteoporotic back pain (79 %), osteoarthritic joint pain (87.65 %), and gastrointestinal disorders like constipation, abdominal pain and chest pain were (66.7%), (53%), and (56.8%) respectively.Keywords: Bone, Joint, Inflammatory Bowel Disorders, Angiotensin.